Associations Between Gestational Diabetes Mellitus Risk and Folate Status in Early Pregnancy and MTHFR C677T Polymorphisms in Chinese Women - Liu PJ (Dove Medical Press, 2020)
Peng Ju Liu,1 Yanping Liu,1,* Liangkun Ma,2,* Ai Min Yao,3 Xiao Yan Chen,4 Yi Xuan Hou,5 Li Ping Wu,5 Liang Yu Xia6 1Department of Clinical Nutrition, Peking Union Medical College Hospital, China Academic Medical Science and Peking Union Medical College, Beijing 100730, People’s Republic of China; 2Department of Gynaecology and Obstetrics, Peking Union Medical College Hospital, China Academic Medical Science and Peking Union Medical College, Beijing 100730, People’s Republic of China; 3Department of Gynaecology and Obstetrics, Shunyi District Maternal and Child Health Hospital, Beijing, People’s Republic of China; 4Department of Gynaecology and Obstetrics, Quanzhou Maternal and Child Health Hospital, Fujian, People’s Republic of China; 5Peking Union Medical College School of Nursing, Beijing, People’s Republic of China; 6Department of Clinical Laboratory, Peking Union Medical College Hospital, China Academic Medical Science and Peking Union Medical College, Beijing 100730, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanping Liu; Liangkun Ma Tel +86-10-69159081Fax +86-10-69155551Email liuyp1227@vip.sina.com; maliangkun@pumch.cnPurpose: Red blood cell (RBC) folate indicates long-term folate intake, and methylenetetrahydrofolate reductase (MTHFR) gene is the main gene affecting folate status. Increasing evidence suggests an association between gestational diabetes mellitus (GDM) and increased folate levels. Whether RBC folate concentrations in the first trimester of pregnancy or polymorphisms of MTHFR C677T (rs1801133) affect GDM risk in Chinese pregnant women remains unknown. Therefore, we analyzed the associations of RBC folate concentrations and rs1801133 polymorphisms with GDM risk among pregnant women in China.Methods: A total of 366 women with a singleton pregnancy were followed prospectively from their first prenatal visit to delivery. RBC folate concentrations and rs1801133 polymorphisms were assessed during the first trimester of pregnancy. Binary logistic regression analyses were performed to determine the odds ratios (ORs) of GDM and 95% confidence intervals (CIs) by using the RBC folate concentration quartiles and rs1801133 polymorphisms.Results: Participants with the TT genotype had the highest RBC folate concentrations. Those with heterozygous or homozygous variants did not have a significantly higher risk of GDM than did women with C alleles. After adjustments for covariates, women in the highest quartile for RBC folate concentration had a higher risk of GDM (adjusted OR = 2.473, 95% CI = 1.013– 6.037, P = 0.047) than did those in the lowest quartile, but this association was nonsignificant after adjustment for rs1801133 polymorphisms.Conclusion: Higher RBC folate, partly caused by MTHFR 677C→T, may be associated with increased GDM risk, even in early pregnancy. Assessing RBC folate status and appropriately supplementing folate during early pregnancy, particularly for patients with MTHFR 677C→T, may prevent GDM. Further studies with larger populations are warranted.Keywords: gestational diabetes mellitus, folic acid, folate, red blood cell folate, methylenetetrahydrofolate reductase, MTHFR